Pengaruh Promosi, Harga, Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian di Shopee - Nur Mentari; Deri Hatta; Rika Mitaliani (Suria Academic Press, 2026)
This study aims to analyze the effects of brand image, price, product quality, and promotion on purchasing decisions on Shopee. The study is a case study involving students of STIE Perdagangan Padang. The research sample consisted of 120 students from STIE Perdagangan Padang. The method employed was a quantitative approach by collecting numerical data, which were analyzed using statistical techniques with SPSS version 27. The results indicate that the four variables price, brand image, promotion, and product quality independently have a positive and significant effect on purchasing decisions at a significance level of α = 0.05. The price variable shows a correlation coefficient of 0.778, promotion (X2) of 0.723, brand image (X3) of 0.804, and product quality (X4) of 0.785, with a significance value (2-tailed) of 0.000 for each variable.